Inovation of Vocational High School 1 Kalibawang, Wonosobo in the economics recovery of pandemic covid-19 - Aftrino Ridlo Hidayat (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The covid-19 pandemic erupted throughout the district of Wonosobo. Economic sector isthe one of sector that gets special attention after the health care. Wonosobo's economy isin crisis situation, affected from both, inside and outside the region. This big problemshould receive immediate attention to avoid further deterioration. Through qualitativedescriptive studies, the paper was aiming for reveal the natural resources at Wonosobothat can be used for economic recovery after the covid-19 pandemic. Wonosobo regencywhich has a wealth of natural resources and people wo work as a farm, so the economicrecovery strategies can rely on the agricultural sector and the people's business sectors onworthy commodities. In terms of economic recovery in this difficult situation not only theresponsibility of the country. The program from Vocational High School One KalibawangWonosobo to build a villages is one of the economic recovery innovation. This innovation isa form of cooperation between SMK N 1 Kalibawang and the village community.